DETERMINANTS OF TAXPAYER COMPLIANCE FACTORS IN BOTTLED DRINKING WATER COMPANIES - Sigit Mareta; Dantarini Mutiasari (Fakultas Bisnis dan Ilmu Sosial Universitas Dian Nusantara, 2023)
This study aims to test whether the level of understanding of taxation, understanding of tax accounting, application of accounting and tax systems affects taxpayer compliance. This research is expected to contribute to increasing the level of compliance of taxpayers to the State. This research method uses a quantitative approach in associative form with the collection of questionnaire result data. The population in this study was determined by purposive sampling technique, where data obtained from the distribution of questionnaires. The data is used as primary data. The data analysis used was multiple linear regression with the help of SPSS 24 software. In this study obtained the results that understanding taxation, understanding tax accounting, application of accounting systems and taxes simultaneously to taxpayer compliance. Understanding taxation, understanding tax accounting has a significant effect on taxpayer compliance, while the application of accounting and tax systems does not have a significant effect on taxpayer compliance.